УМОВИ РОЗВИТКУ МИСЛЕННЯ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2002)
The article is devoted to the problem of development of thinking in modern general school The author notes the incorrectness ofstereotype approaches to the appraisement of forming levels of pupils' thinking culture. Spessial importance of this task for senior pupils is stressed. Further, the forming of thinking characteristics and operations in the course of comprehending of knowledge are examined. Then the author analyses the conception of «develop of thinking» in psychological & pedagogical literature. He comes to the conclusion about necessity to set the concrete aims for this and to choose the suitable teaching forms which are based on theoretical & methodological grounds.